Robotic Realities: Near Term Prospects and Problems - AYRES, Robert U. (Institutional Knowledge at Singapore Management University, 1983)
Industrial robots are automation, but with a difference. Other machine tools are extensions of human capabilities, while robots are seen mainly as substitutes for human workers. Robots will find most of their industrial applications during the next decade or two in the metal-working sectors, where they will begin to displace semiskilled machine operatives in medium to large batch production operations. They cannot substitute for skilled machinists or other workers doing nonroutine jobs, or specialized, dedicated hard automation used in mass production. The current generation of robots, lacking sensory data processing and interpretation capabilities, can potentially replace up to 1.3 million manufacturing jobs. The next generation, with crude vision or tactile senses; will potentially displace about 3 million more. However, only relatively large firms can profitably utilize many robots at present; it may be 20 years or more before these usage rates are achieved in practice. A shift from stand-alone machine tools, to manufacturing cells consisting of several machine tools served by a robot and controlled by a computer, will accelerate the practical use of robots in the 1990s.